Reused Cultivation Water Accumulates Dissolved Organic Carbon and Uniquely Influences Different Marine Microalgae - Loftus, Sarah E.; Johnson, Zackary I. (Frontiers in Bioengineering and Biotechnology, 2019)
Reusing growth medium (water supplemented with nutrients) for microalgae cultivation is required for economical and environmentally sustainable production of algae bioproducts (fuels, feed, and food). However, reused medium often contains microbes and dissolved organic matter that may affect algae growth. While the accumulation of dissolved organic carbon (DOC) in reused medium has been demonstrated, it is unclear whether DOC concentrations affect algae growth or subsequent rates of algal DOC release. To address these questions, lab-scale experiments were conducted with three marine microalgae strains, Navicula sp. SFP, Staurosira sp. C323, and Chlorella sp. D046, grown in medium reused up to four times. Navicula sp. and Chlorella sp. grew similarly in reused medium as in fresh medium, while Staurosira sp. became completely inhibited in reused medium. Across the three algae, there was no broad trend between initial DOC concentration in reused medium and algae growth response. Navicula sp. released less DOC overall in reused medium than in fresh medium, but DOC release rates did not decrease proportionally with increased DOC concentrations. Net DOC accumulation was much lower than gross DOC released by Navicula sp. and Staurosira sp., indicating the majority of released DOC was degraded. Additionally, biodegradation experiments with reused media showed no further net decrease in DOC, suggesting the accumulated DOC was recalcitrant to the associated bacteria. Overall, these results suggest that taxa-specific factors may be responsible for algae growth response in reused medium, and that DOC release and accumulation are insensitive to prior cultivation rounds. Choosing an algae strain that is uninhibited by accumulated DOC is therefore critical to ensure successful water reuse in the algae industry.